2020
DOI: 10.3390/w12113286
|View full text |Cite
|
Sign up to set email alerts
|

The Water Footprint of the United States

Abstract: This paper commemorates the influence of Arjen Y. Hoekstra on water footprint research of the United States. It is part of the Special Issue “In Memory of Prof. Arjen Y. Hoekstra”. Arjen Y. Hoekstra both inspired and enabled a community of scholars to work on understanding the water footprint of the United States. He did this by comprehensively establishing the terminology and methodology that serves as the foundation for water footprint research. His work on the water footprint of humanity at the global scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 101 publications
0
16
0
Order By: Relevance
“…The impact of different irrigation systems on the wheat WF in China was evaluated; results showed that micro irrigation had a lower WF compared to that of furrow and sprinkler systems. Recent studies proved that cropping pattern and cropping calendar have the potential to enhance water use efficiency, water productivity, and WF [29,[75][76][77][78]. We recommend a comprehensive national study to assess all these possible alternatives of efficient water use to find sustainable strategies to enhance the water productivity and reduce the WF of crop production.…”
Section: Practical Implicationsmentioning
confidence: 98%
“…The impact of different irrigation systems on the wheat WF in China was evaluated; results showed that micro irrigation had a lower WF compared to that of furrow and sprinkler systems. Recent studies proved that cropping pattern and cropping calendar have the potential to enhance water use efficiency, water productivity, and WF [29,[75][76][77][78]. We recommend a comprehensive national study to assess all these possible alternatives of efficient water use to find sustainable strategies to enhance the water productivity and reduce the WF of crop production.…”
Section: Practical Implicationsmentioning
confidence: 98%
“…Recent studies have proved that cropping pattern have the potential to enhance water use efficiency, water productivity, and water footprint (Nouri et al, 2020;Konar and Marston, 2020). According to Simpson (2010), agronomic practices are management processes such as intercropping, contour cultivation, minimum tillage, mulching and manuring undertaken within the cropping area.…”
Section: Agronomic Practices For Improved Soil Water Managementmentioning
confidence: 99%
“…This research confirms the positive contribution of education to WFP. Education has been recently characterized as an instrument that will lower the WFP across human communities [60][61][62]. Therefore, it is essential to encourage educated farmers to participate in irrigation farming, to improve their WFP in the face of climate change.…”
Section: Yield and Water Footprintmentioning
confidence: 99%